The Implementation of syirkah agreements in agricultural financing for enhancing the rural economy: insights from South Sumatera - Engga, Apri; Budiyoko; Madiyoh, Abdulhakim; Afrianto, Whisnu Febry (Journal of Halal Product and Research (JHPR), 2023)
The agricultural sector continues to be the primary driver of rural economies in Indonesia. Despite its vital role, the rural agricultural sector often faces serious challenges in terms of adequate financing. This study examines the implementation of the syirkah agreement as an alternative financing model in the agricultural sector to enhance rural economies. Using a phenomenological approach, this research involves in-depth interviews and direct observations regarding the application of the syirkah agreement in financing a rice milling unit managed by the Farmers' Group Association (Gapoktan) in Pandan Village, Tanah Abang District, Penukal Abab Lematang Ilir Regency, South Sumatra. The research findings indicate that the application of the syirkah agreement in agricultural financing has yielded significant positive impacts. It enables farmers to have easier access to capital and necessary resources for productivity enhancement while promoting active farmer participation in their agricultural business decision-making. These results underscore the crucial role of the syirkah agreement in creating a sustainable and inclusive rural economy, in line with the principles of economic justice in sharia law.